Human Dendritic Cell Functional Specialization in Steady-State and Inflammation - Boltjes, Arjan; Van Wijk, Femke (Frontiers in Immunology, 2014)
Dendritic cells (DC) represent a heterogeneous population of antigen-presenting cells that are crucial in initiating and shaping immune responses. Although all DC are capable of antigen uptake, processing and presentation to T cells, DC subtypes differ in their origin, location, migration patterns, and specialized immunological roles. While in recent years there have been rapid advances in understanding DC subset ontogeny, development, and function in mice, relatively little is known about the heterogeneity and functional specialization of human DC subsets, especially in tissues. In steady-state, DC progenitors deriving from the bone marrow give rise to lymphoid organ-resident DC and to migratory tissue DC that act as tissue sentinels. During inflammation additional DC and monocytes are recruited to the tissues where they are further activated and promote T helper cell subset polarization depending on the environment. In the current review we will give an overview of the latest developments in human DC research both in steady-state and under inflammatory conditions. In this context we review recent findings on DC subsets, DC-mediated cross-presentation, monocyte-DC relationships, inflammatory DC development and DC-instructed T cell polarization. Finally we discuss the potential role of human DC in chronic inflammatory diseases.